If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -45 + 5x = 6x + 32 Reorder the terms: -45 + 5x = 32 + 6x Solving -45 + 5x = 32 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -45 + 5x + -6x = 32 + 6x + -6x Combine like terms: 5x + -6x = -1x -45 + -1x = 32 + 6x + -6x Combine like terms: 6x + -6x = 0 -45 + -1x = 32 + 0 -45 + -1x = 32 Add '45' to each side of the equation. -45 + 45 + -1x = 32 + 45 Combine like terms: -45 + 45 = 0 0 + -1x = 32 + 45 -1x = 32 + 45 Combine like terms: 32 + 45 = 77 -1x = 77 Divide each side by '-1'. x = -77 Simplifying x = -77
| -95.31=x/3 | | 4/7*14/8(y-2) | | 11x-19=23 | | 4log(x)-6=2log(x) | | 23=5(x+3) | | 4lg(x)-6=2lg(x) | | gx=144 | | (x+1)(x-2)=(x-1)(x-1) | | -5/6=3/4n | | (3x-1)/(x-4)=0 | | 5x-8=3x-11+8 | | 2z-12-1=z-25+z | | 3/1728 | | 6(-2-3x)+8= | | -x-4=3x+6 | | -3-3x/21 | | 2(3m-9)-3(m-2)= | | 4x+5=8x+5 | | 7x-2=9x-4 | | 9x-9=19x-19 | | 11x-12=13x-20 | | 6x+3y=153 | | x+y=1.23 | | 5-x=32 | | 2x+15=13x+1 | | 10x+(12-x)=9x+12 | | 5x-1=10x-17 | | 19x+2=3x+14 | | 10/x=6.3681 | | 4.6/y=44.16 | | -32*Y=-22336 | | 10y+15x=5 |